Fresno County Bar Association Annual Bar Banquet Held at TorNino's - Watkins, Howard::::::::: (1989)
Fresno County Bar Association President G. Dana French shaking hands with Rene Lastreto II after giving him Appreciation Plaque for his service on Fresno County Bar Association's Board of Directors; Seated is Fresno County Bar Association Secretary John Hames